Fluid dynamic lateral slicing of high tensile strength carbon nanotubes - Vimalanathan, K.; Gascooke, J.; Suarez-Martinez, Irene; Marks, N.; Kumari, H.; Garvey, C.; Atwood, J.; Lawrance, W.; Raston, C. (Nature Publishing Group, 2016)
Lateral slicing of micron length carbon nanotubes (CNTs) is effective on laser irradiation of the materials suspended within dynamic liquid thin films in a microfluidic vortex fluidic device (VFD). The method produces sliced CNTs with minimal defects in the absence of any chemical stabilizers, having broad length distributions centred at ca 190, 160 nm and 171 nm for single, double and multi walled CNTs respectively, as established using atomic force microscopy and supported by small angle neutron scattering solution data. Molecular dynamics simulations on a bent single walled carbon nanotube (SWCNT) with a radius of curvature of order 10 nm results in tearing across the tube upon heating, highlighting the role of shear forces which bend the tube forming strained bonds which are ruptured by the laser irradiation. CNT slicing occurs with the VFD operating in both the confined mode for a finite volume of liquid and continuous flow for scalability purposes.